WT1 as an immunotherapy target for thymic epithelial tumors: a novel method to activate anti-tumor immunity - Takahashi, Nobuyuki; Zhao, Chen; Rajan, Arun (Mediastinum; Vol 3 (April 2019): Mediastinum, 2019)
Thymic epithelial tumors (TETs) are family of rare cancers that exhibit diverse histology and variable clinical behavior (1). A significant fraction of patients, especially those with thymic carcinoma, have locally-advanced or metastatic disease at diagnosis that is often unresectable (1). Chemotherapy is associated with objective response rates (ORR) of 50–90% in the front-line setting, but limited benefit is observed in patients with recurrent disease (1,2). With few exceptions, biological agents have not demonstrated clinically meaningful activity in relapsed or refractory TETs (3). A low tumor mutation burden and paucity of actionable biological targets creates challenges for the development of targeted therapies for TETs (4,5). Hence, there is a pressing need to develop new treatments, especially for patients with advanced thymic carcinomas.